Prime Minister Decree No. 2130 of the Year 2025 - Prime Minister (The Middle East Library For Economic Services, 2025)
Thursday corresponding to 3 July, 2025 (AD) shall be considered an official paid holiday at the ministries, government departments, public authorities, local administrative units, public sector companies and public business sector companies, instead of Monday corresponding to 30 June, 2025 (AD), on the occasion of the Anniversary of June 30 Revolution. Meanwhile, the examination works shall continue to take place according to the schedule set by the competent authority.